Chiral Perovskite: Chiral Perovskites: Promising Materials toward Next‐Generation Optoelectronics (Small 39/2019). Issue 39 (25th September 2019) - Dong, Yuze; Zhang, Yupeng; Li, Xinyue; Feng, Yaqing; Zhang, Han; Xu, Jialiang
Abstract : The introduction of chirality into perovskite scaffolds, leading to the generation of chiral perovskites, is an immense step forward toward the development of smart optoelectronic and spintronic materials and devices. In article number 1902237, Han Zhang, Jialiang Xu, and co‐workers review the design and construction of chiral perovskites along with their optoelectronic properties.